[Burr, Marilyn (ballet dancer) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Further programs relating to Marilyn Burr are located within the PROMPT file for London Festival Ballet.
Marilyn Burr became a solist with the London Festival Ballet in 1952. She was promoted to a Principal Dancer in 1953, and then spent a decade with the company. Further programs featuring Marilyn Burr are located in a seperate PROMPT file for the London Festival Ballet. [Information from Karl Levett.]
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Burr, Marilyn -- Miscellanea; Ballet dancers -- Australia -- Miscellanea; Dancers -- Australia; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian